Karakterisasi Ekstrak Daun Bidara (Ziziphus mauritiana L.) Berdasarkan Jenis Pelarut Dan Ukuran Partikel Pada Metode Microwave Assisted Extraction - Meriana, Gusti Ayu Made; Wartini, Ni Made; Triani, I Gusti Ayu Lani (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2026)
Bidara leaves (Ziziphus mauritiana L.) contain bioactive compounds such as saponins that have the potential to act as natural antioxidants. These compounds can be extracted using the Microwave Assisted Extraction method. This study aimed to determine the effect of solvent type and particle size on the characteristics of bidara leaf extract and to obtain the best solvent type and particle size for produce bidara leaf extract using the Microwave Assisted Extraction method. The experimental design used was a factorial Randomized Block Design (RDB) with 2 factors, namely solvent type consisting of (methanol, ethanol, and acetone), and particle size consisting of (40, 60, and 80 mesh). The data were analyzed using analysis of variance (ANOVA) and followed by Duncan Multiple Range Test (DMRT) if the treatments had a significant effect on the observed variables. The results showed that the solvent type and particle size affected the yield, crude extract saponin content, foam height, and antioxidant capacity. The interaction between treatments affected the crude extract saponin content, foam height, and antioxidant capacity but had no effect on the yield. The best treatment for producing bidara leaf extract as a source of saponin using the Microwave Assisted Extraction method based on the effectiveness index test was obtained from methanol solvent and 80 mesh particle size with the extract characteristics of yield 33.41±0.53%, crude extract saponin content 56.46±0.40%, foam height 25.83±0.71 mm, and antioxidant capacity 10.34±0.57 mg GAEAC/g.